2010
DOI: 10.1097/tp.0b013e3181ff500d
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Prophylaxis With Valganciclovir Is Cost Effective in Reducing Posttransplant Cytomegalovirus Disease Within the United States

Abstract: Prolonged prophylaxis with valganciclovir reduces the incidence of events associated with CMV infection in high-risk kidney transplant recipients and is a cost-effective strategy in CMV disease management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 39 publications
(39 reference statements)
0
20
0
Order By: Relevance
“…A recently published randomized trial proved the clinical superiority of 6-month valganciclovir prophylaxis compared to a 3-month course in high-risk renal transplant recipients [30]. Cost-effectiveness analyses showed the advantage of 6-month prophylaxis in quality-adjusted life years in a 5- to 10-year period using Markov model [25,31]. However, the limitation of such analyses lies in the use of clinical probabilities of graft failure and death in association with CMV disease from different studies, which may vary significantly among different transplant centers or immunosuppressive regimens.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published randomized trial proved the clinical superiority of 6-month valganciclovir prophylaxis compared to a 3-month course in high-risk renal transplant recipients [30]. Cost-effectiveness analyses showed the advantage of 6-month prophylaxis in quality-adjusted life years in a 5- to 10-year period using Markov model [25,31]. However, the limitation of such analyses lies in the use of clinical probabilities of graft failure and death in association with CMV disease from different studies, which may vary significantly among different transplant centers or immunosuppressive regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the pre-emptive strategy prophylaxis is logistically easier, with lesser monitoring cost, but higher cost of drug therapy [11]. Overall, the universal prophylaxis (especially for 200 days duration) was cost-effective when indirect benefits were also accounted for [19,20]. Problems with prophylactic strategy include frequent leucopenia, increase in late onset CMV disease, and emergence of resistant CMV.…”
Section: Cytomegalovirus Diseasementioning
confidence: 99%
“…A metaanalysis of 11 randomized trials (698 patients; median follow-up: 12 months, range: 3-22 months), with six randomized trials (302 patients) after kidney transplantation, demonstrated a beneficial effect of the prophylactic use of CMV immunoglobulin on total survival and prevention of Should not be used 1500 mg once a day, or 500 mg three times a day Should not be used 1000 mg once a day, or 500 mg twice a day [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Should not be used 500 mg once a day <10…”
Section: Antiviral Medications For Universal Prophylaxis and Preemptimentioning
confidence: 99%
“…Thus, universal prophylaxis resulted in a cost saving of $27 967 per qualityadjusted life year gained when compared with preemptive therapy. Using data from the Improved Protection Against CMV in Transplant (IMPACT) trial demonstrated that prolonged prophylaxis of 200 days with valganciclovir compared with 100 days significantly reduces the incidence of CMV in high-risk kidney transplant (D+/R−) recipients; a cost-effectiveness model was developed to evaluate prolonged prophylaxis (200 days) with valganciclovir and its long-term economic impact from the US healthcare payer perspective (16). For the first 5 years, they found that the incremental cost-effectiveness ratio of US $14 859/qualityadjusted life year suggests that 200-day valganciclovir prophylaxis is cost effective compared with the 100-day regimen, considering a threshold of US $50 000 per qualityadjusted life year.…”
Section: Universal Prophylaxis and Preemptive Therapymentioning
confidence: 99%